IMPORTANCE OF POSITIVE PEDAGOGICAL RELATIONSHIPS IN THE CONTEXT OF NOWADAY`S TEACHER EDUCATION - Bethere, Dina; Pavitola, Linda; Ulmane-Ozolina, Lasma (European Scientific Journal, ESJ, 2014)
The current situation in the sphere of education outlines the need for changes that can be seen as a continuous quality improvement process in the sphere of teacher education. The context emphasizes pedagogical relationships that are viewed as a key element penetrating the whole process of education. However, the competence models focus more on different sets of competences, but those necessary for the development of pedagogical relationships remain unclear. Therefore the following research questions have been put forward: 1) What is the correlation between pedagogical relationships oriented towards the personality and university teachers as social role models for student teachers? 2) What is the correlation between pedagogical relationships oriented towards the personality and self-evaluation of the effectiveness of mastering the content of study courses? The article reflects the research study that involves Bachelor and Master level students at Liepaja University, who were separated in 3 groups according to the respondents’ pedagogical experience and the following criterions: 1) a level of study experience and 2) personal involvement into the development of pedagogical relationships. The results were collected by Likert-type questionnaire and analysed with SPSS Statistics 17.0 using a crosstabulation and a Pearson’s chi-square test. The totality of the research data confirm that exactly the skills of university teachers to create positive personal relationships with the students can be regarded as a precondition for achieving desirable study outcomes and a determinant factor of their competitiveness.